2021
DOI: 10.1111/gcb.15972
|View full text |Cite
|
Sign up to set email alerts
|

Low statistical power and overestimated anthropogenic impacts, exacerbated by publication bias, dominate field studies in global change biology

Abstract: Field studies are essential to reliably quantify ecological responses to global change because they are exposed to realistic climate manipulations. Yet such studies are limited in replicates, resulting in less power and, therefore, potentially unreliable effect estimates. Furthermore, while manipulative field experiments are assumed to be more powerful than non-manipulative observations, it has rarely been scrutinized using extensive data. Here, using 3847 field experiments that were designed to estimate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 104 publications
4
33
0
Order By: Relevance
“…In our examples, the mean detected interaction effect size only approaches the true interaction effect size at around n = 40, and at small sample sizes the mean detected effect size is approximately three times the magnitude of the true effect size (Figure 5b ). This shows how publishing only statistically significant results from experiments with low sample sizes leads to an overestimation of nonadditivity, a problem that has also been highlighted for biological responses to single stressors (Yang et al, 2022 ).…”
Section: Statistical Powermentioning
confidence: 72%
See 3 more Smart Citations
“…In our examples, the mean detected interaction effect size only approaches the true interaction effect size at around n = 40, and at small sample sizes the mean detected effect size is approximately three times the magnitude of the true effect size (Figure 5b ). This shows how publishing only statistically significant results from experiments with low sample sizes leads to an overestimation of nonadditivity, a problem that has also been highlighted for biological responses to single stressors (Yang et al, 2022 ).…”
Section: Statistical Powermentioning
confidence: 72%
“…Commonplace sample sizes (e.g., 4 replicates per treatment) are not adequate for this question (Figures 4 and 5 ), and the researcher will likely need to implement sample sizes that are multiple (two or more) times larger than those commonly used. There may be other situations where a smaller effect is not so important, implying smaller samples are adequate, such as monitoring abundance declines in a system with high functional redundancy, but even here, care needs to be taken since concerns have been raised regarding publication bias leading to the overestimation of stressor effects from experiments with small sample sizes (Figure 5b , Yang et al, 2022 ).…”
Section: Smallest Interaction Of Interest: What Is a Biologically Mea...mentioning
confidence: 99%
See 2 more Smart Citations
“…This biased publishing can result in the proliferation of studies reporting strong effects, even though they may not be true [26] and can fuel citation bias [27]. Indeed, a recent analysis suggested that field studies in global change biology suffer from publication bias, which has fuelled the proliferation of underpowered studies reporting overestimated effect sizes [28]. To determine if studies testing for effects of ocean acidification on fish behavior exhibited signs of publication bias and citation bias, we assessed relationships between effect size magnitude, journal impact factor, and Google Scholar citations (Fig 4).…”
Section: Plos Biologymentioning
confidence: 99%